1995
DOI: 10.1038/376174a0
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal GABA transporter function in temporal-lobe epilepsy

Abstract: Electrophysiological studies of human temporal-lobe epilepsy suggest that a loss of hippocampal GABA-mediated inhibition may underlie the neuronal hyperexcitability. However, GABA (gamma-aminobutyric acid)-containing cells are preserved and GABA receptors are maintained in the surviving hippocampal neurons. Diminished GABA release may therefore mediate the loss of inhibition. Here we show that, in the human brain, potassium-stimulated release of GABA was increased, and glutamate-induced, calcium-independent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(169 citation statements)
references
References 22 publications
6
160
0
3
Order By: Relevance
“…The large increase in extracellular [GABA] after the fusion of synaptic vesicles would be expected to drive reuptake, but when extracellular [GABA] is low, nonvesicular GABA efflux commonly may occur at relatively low firing rates. Previous studies also have suggested that nonvesicular GABA efflux can be functionally important under some conditions (Schwartz, 1987;Taylor and Gordon-Weeks, 1991;During et al, 1995;Drew et al, 1997).…”
Section: Functional Role Of the Gaba Transportermentioning
confidence: 99%
See 1 more Smart Citation
“…The large increase in extracellular [GABA] after the fusion of synaptic vesicles would be expected to drive reuptake, but when extracellular [GABA] is low, nonvesicular GABA efflux commonly may occur at relatively low firing rates. Previous studies also have suggested that nonvesicular GABA efflux can be functionally important under some conditions (Schwartz, 1987;Taylor and Gordon-Weeks, 1991;During et al, 1995;Drew et al, 1997).…”
Section: Functional Role Of the Gaba Transportermentioning
confidence: 99%
“…An increased number of GABA transporters in the plasma membrane would increase the flux of GABA under the force of a constant [GABA] gradient. Conversely, within the seizure focus of human temporal lobe epilepsy patients there is evidence for a decrease in the number of functional GABA transporters (During et al, 1995), which could contribute to seizure generation or spread. It is likely that a variety of other factors could modulate GABA transporter number or alter the function of those transporters that are present.…”
Section: Anticonvulsant Mechanism Of Vigabatrinmentioning
confidence: 99%
“…Human studies indicated that GABA transporter function is reduced in epileptic hippocampi (During et al, 1995;Williamson et al, 1995). This may result from a reversed GABA transport due to membrane depolarization.…”
Section: Transporters As Pharmacological Targetsmentioning
confidence: 99%
“…Recent evidence suggests that the GABA uptake is reduced in tissue from animals and humans with ' Author for correspondence. chronic temporal lobe epilepsy (Janjua et al, 1991;During et al, 1995). This should lead to prolonged synaptic inhibition and might reflect an adaptation to hyperexcitability.…”
Section: Introductionmentioning
confidence: 99%